A HOLISTIC–ECOLOGICAL PERSPECTIVE ON THE JUNIOR-TO-SENIOR TRANSITION IN FOOTBALL - NEMEȘ, Raul-Alexandru; BICHESCU, Andrade-Ionuț (Studia Universitatis Babeş-Bolyai Educatio Artis Gymnasticae, 2025)
Introduction: The transition from youth to senior football represents a complex process of psychological, social, and performance adaptation. A holistic–ecological approach emphasizes that this passage depends not only on technical readiness but also on motivational and self-regulatory development. Objective: This study aimed to evaluate the impact of the Personal Development Plan (PDP) and Personal Action Plan (PAP) on the psychological readiness, motivation, and self-efficacy of a youth player transitioning to senior football within FC Universitatea Cluj Academy. Material and Methods: A single-case longitudinal design was applied during the 2024–2025 season with a 17-year-old left winger. The intervention combined individualized PDP and PAP implementation with three assessment stages using the Sport Motivation Scale II (SMS-II), Athlete Self-Efficacy Scale (ASES), monthly reflection logs, and coach evaluations. Quantitative data were analyzed descriptively, while qualitative reflections were interpreted thematically. Results: The findings showed consistent growth in intrinsic motivation, integrated regulation, and all four dimensions of self-efficacy. Reflection logs and coach reports confirmed improvements in emotional control, communication, and self-regulated learning. By the end of the monitored season, the athlete achieved professional readiness and made his official debut in Romania’s top division (Liga I) in September 2025. Discussion: The results confirm that structured PDP and PAP frameworks, supported by reflective practice and psychological monitoring, enhance athletes’ motivation, confidence, and adaptability during transition. Conclusions: The study highlights the effectiveness of holistic, individualized development planning in facilitating sustainable progression from youth to senior football.